In situ architecture of a nucleoid-associated biomolecular co-condensate that regulates bacterial cell division - Peng Xu; Dominik Schumacher; Chuan Liu; Andrea Harms; Marcel Dickmanns; Florian Beck; Jürgen M. Plitzko; Wolfgang Baumeister; Lotte Søgaard-Andersen (Proceedings of the National Academy of Sciences, 2025)
In most bacteria, cell division depends on the tubulin-homolog FtsZ that polymerizes in a GTP-dependent manner to form the cytokinetic Z-ring at the future division site. Subsequently, the Z-ring recruits, directly or indirectly, all other proteins of the divisome complex that executes cytokinesis. A critical step in this process is the precise positioning of the Z-ring at the future division site. While the divisome proteins are generally conserved, the regulatory systems that position the Z-ring are more diverse. However, these systems have in common that they modulate FtsZ polymerization. In Myxococcus, PomX, PomY, and PomZ form precisely one MDa-sized, nonstoichiometric, nucleoid-associated assembly that spatiotemporally guides Z-ring formation. Here, using cryo-correlative light and electron microscopy together with in situ cryoelectron tomography, we determine the PomXYZ assembly’s architecture at close-to-live conditions. PomX forms a porous meshwork of randomly intertwined filaments. Templated by this meshwork, the phase-separating PomY protein forms a biomolecular condensate that compacts and bends the PomX filaments, resulting in the formation of a selective PomXYZ co-condensate that is associated to the nucleoid by PomZ. These studies reveal a hitherto undescribed supramolecular structure and provide a framework for understanding how a nonstoichiometric co-condensate forms, maintains number control, and nucleates GTP-dependent FtsZ polymerization to precisely regulate cell division.